PENINGKATAN HUBUNGAN SOSIAL ANTAR TEMAN SEBAYA MELALUI LAYANAN BIMBINGAN KELOMPOK DI SMP NEGERI 26 SURABAYA (PSIKOLOGI KONSELING, 2022)
SMP Negeri 26 Surabaya students look some students can establish social relationships well and there are students who are not able to establish good social relationships, so it is necessary to have group dynamics that are deliberately developed because group dynamics are interpersonal relationships characterized by a spirit of cooperation between group members. , share knowledge, experience and achieve group goals, so that through group dynamics the ability to communicate and socialize with peers can be improved. With this type of experimental research on class VIII students of SMP Negeri 26 Surabaya, with a study group of 10 classes, each class has 38 students, so the population of class VIII is 380 students. The samples taken in this study were 38 students. The results showed that the level of social relations between students' peers before receiving group guidance services (treatment) was in the high or good category; as well as the level of social relations between students' peers after receiving group guidance services classified in the very high or very good category.
Keywords: Social Relations; Peers; and Group Guidance.